Auf dem Weg ins Türkische Reich Ein bildungshistorisches Lesebuch - Lohmann, Ingrid; Böttcher, Julika (Wie die Türken in unsere Köpfe kamen. Eine deutsche Bildungsgeschichte, 2022)
"Lese-Buch - a strange name; what does it mean?" asks Elberfeld seminary teacher Hermann Wendt in 1909 in the "Deutsche Blätter für erziehenden Unterricht. ""A book in which one reads?" But to be read is the purpose of all books! The editors present excerpts from the corpus of sources they used to investigate how knowledge about Turks and Turkey shaped and changed in earlier periods of German history. The book documents views about Turks and Turkey up to the period after World War I - especially on the part of pedagogues and teachers. It invites readers to familiarize themselves with a chapter of the tense but hitherto little-known interweaving of German colonial and educational history.